2000
DOI: 10.1152/jn.2000.83.6.3230
|View full text |Cite
|
Sign up to set email alerts
|

Reaching During Virtual Rotation: Context Specific Compensations for Expected Coriolis Forces

Abstract: Subjects who are in an enclosed chamber rotating at constant velocity feel physically stationary but make errors when pointing to targets. Reaching paths and endpoints are deviated in the direction of the transient inertial Coriolis forces generated by their arm movements. By contrast, reaching movements made during natural, voluntary torso rotation seem to be accurate, and subjects are unaware of the Coriolis forces generated by their movements. This pattern suggests that the motor plan for reaching movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 14 publications
5
34
1
1
Order By: Relevance
“…Some movements, such as those made to reach a virtual object or to wave to virtual avatars, might suggest that participants actually believe that they are within the VE. Hence, postural movements seem to be an interesting indicator of presence, as reported by other authors (Cohn, DiZio, & Lackner, 2000;Held & Durlach, 1993;Prothero, Parker, Furness, & Wells, 1995;Sheridan, 1992;Slater, Usoh, & Steed, 1995). Nichols, Haldane, and Wilson (2000) visually classified participants' reactions to a startling event and found that the results of this measurement correlated positively with the reported sense of presence.…”
Section: Presence Measurementsupporting
confidence: 68%
See 1 more Smart Citation
“…Some movements, such as those made to reach a virtual object or to wave to virtual avatars, might suggest that participants actually believe that they are within the VE. Hence, postural movements seem to be an interesting indicator of presence, as reported by other authors (Cohn, DiZio, & Lackner, 2000;Held & Durlach, 1993;Prothero, Parker, Furness, & Wells, 1995;Sheridan, 1992;Slater, Usoh, & Steed, 1995). Nichols, Haldane, and Wilson (2000) visually classified participants' reactions to a startling event and found that the results of this measurement correlated positively with the reported sense of presence.…”
Section: Presence Measurementsupporting
confidence: 68%
“…The studies have attempted to measure behaviors such as reactions with an avatar (Bailenson et al, 2001;Bailenson et al, 2008), in order to measure social presence; movements to avoid a danger such as a virtual cliff (Slater, Usoh, & Steed, 1995); or induced movements or vection (Cohn et al, 2000) as a consequence of virtual scenes in movement. Following the approach of objectively estimating presence, we propose a procedure based on measuring reactions to events originated within the VE.…”
Section: Discussionmentioning
confidence: 99%
“…During most active motions the individual and the external world are moving at the same time. While there is ample evidence that dynamic visual inputs affect motor behavior, (e.g., disrupting upper extremity movement trajectory and endpoint [5] and increasing postural instability [6,7]), the weighting of such visual information and the exact role that visual motion plays in human motor control is not well understood. In recent years, virtual reality technology has emerged as a powerful tool to study motor control in healthy subjects and in patients with stroke or labyrinthine deficiency [8][9][10] because it enables us to manipulate the visual world.…”
Section: Introductionmentioning
confidence: 99%
“…In adaptation studies, the internal representation is typically evaluated from the movements of participants following visual or force perturbations. Throughout the adaptation, the participants modify the kinematics and dynamics of their movements to reduce task-related errors and to maximize task success (Krakauer et al, 2000, Cohn et al, 2000, Simani et al, 2007, Shadmehr and Mussa-Ivaldi, 1994. A common way to assess the adaptation and the construction of an internal model is by examining aftereffects when the perturbation is unexpectedly removed.…”
Section: Introductionmentioning
confidence: 99%